Introduction to Symmetric Semigroups and Symmetric Semirings - Dr.A.Punitha Tharani and V.Uma Maheswari (International Journal of Advanced Science and Technology, 2020)
The new concepts  introduced in this paper are symmetric semigroups and symmetric semirings. Some results based on the above concepts are studied here and also we define composite regular and reverse composite regular in symmetric group.